Gambaran Nikotin pada Pra Lansia Perokok Linting (Tembakau) di Desa Pohgading Timur Kecamatan Pringgabaya - Isnaeni, Robiatul; Inayati, Nurul; Anggit jiwantoro, Yudha; Kristinawati, Erna (Journal of Indonesia Laboratory Students (JILTS), 2024)
Background: Cigarettes are a type of tobacco product produced from the Nicotiana Tabacum, Nicotiana Rustica and other species. Cigarettes are cylinder-shaped from paper measuring between 70 – 120 mm long with a diameter of around 10 mm containing chopped tobacco leaves. There are two types of cigarettes, namely hand-rolled cigarettes and electronic cigarettes which are usually called vape or vapor. Objective: To find out the description of nicotine in hand-rolled (tobacco) smokers in East Pohgading village, Pringgabaya subdistrict. Method: The research is a descriptive analytical method. By taking samples using purposive sampling technique. Results: The results of the research that was carried out obtained samples of 42 elderly people who used hand-rolled cigarettes (tobacco), 41 samples were positive and 1 was negative for nicotine. Conclusion: Results from the urine of pre-elderly respondents who smoked hand-rolled (tobacco) were positive for nicotine as many as 41 people and 1 person was negative.